The potential combination of BCL-2 inhibitors and ibrutinib as frontline therapy in chronic lymphocytic leukemia. Issue 10 (3rd October 2017) - Aw, Andrew; Brown, Jennifer R.
Abstract: The recent development of small molecule inhibitors targeted at the B-cell receptor (BCR) pathway and the anti-apoptotic protein BCL-2 has revolutionized the care of patients with chronic lymphocytic leukemia (CLL). While durable responses to the BCR inhibitor ibrutinib have been observed in both previously untreated and relapsed/refractory CLL patients, residual disease is common in patients treated with single-agent ibrutinib. Interest remains high in therapeutic combinations that may lead to better quality remissions. A potential partner to ibrutinib with a distinct mechanism of action that is likely to lead to deeper responses is the BCL-2 inhibitor venetoclax. Preclinical studies have suggested synergism between inhibitors of BCR and BCL-2 and have paved the way to the development of ongoing clinical trials aimed at evaluating the combination of ibrutinib with venetoclax in CLL patients.